Supramolecular Chemistry 2012
DOI: 10.1002/9780470661345.smc072
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid‐Based Receptors

Abstract: The ability to monitor analytes within physiological, environmental, and industrial scenarios is of prime importance. As recognition events occur on a molecular level, gathering and processing the information poses a fundamental challenge. Therefore, robust chemical molecular sensors, known as “chemosensors,” with the capacity to detect chosen molecules selectively and signal this presence continue to attract considerable attention. Real‐time monitoring of saccharides is of particular interest, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 197 publications
0
3
0
Order By: Relevance
“…The co-authors of this report have investigated triazoles as chemosensors and as products of asymmetric synthesis. Furthermore, an interest in boronic acid derivatives as chemosensors, including the use of cross-coupling reactions as a means of sensing, means the co-authors of this report are familiar with boronic acids and esters . As such, a desire to bring together these streams of research under one umbrella has led to the research reported in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…The co-authors of this report have investigated triazoles as chemosensors and as products of asymmetric synthesis. Furthermore, an interest in boronic acid derivatives as chemosensors, including the use of cross-coupling reactions as a means of sensing, means the co-authors of this report are familiar with boronic acids and esters . As such, a desire to bring together these streams of research under one umbrella has led to the research reported in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, boronic acids, which are widely accepted as capture molecules for saccharides [ 68 ], can be modified to achieve a high selectivity for glucose binding. The geminal hydroxyl groups of boronic acids eagerly bind to the cis-diols of various sugar molecules; however, not specifically glucose.…”
Section: Diabetesmentioning
confidence: 99%
“…To enable Anticalins for the recognition of sugar ligands, and to overcome the camouflage effect in aqueous solution, we endeavored the incorporation of boronic acid, which is known to form reversible covalent complexes with cis -diols as they usually occur in saccharides and their derivatives . This type of functional group provides an ideal reagent for selective molecular recognition of sugars and has led to the development of boronic acid-based small-molecule sensors .…”
mentioning
confidence: 99%